3p14 De Novo Interstitial Microdeletion in a Patient with Intellectual Disability and Autistic Features with Language Impairment: A Comparison with Similar Cases - Ana Belén de la Hoz; Hiart Maortua; Ainhoa García-Rives; María Jesús Martínez-González; Maitane Ezquerra; María-Isabel Tejada (Case Reports in Genetics)
To date, few cases of 3p proximal interstitial deletions have been reported and the phenotype and genotype correlation is not well understood. Here, we report a new case of a 3p proximal interstitial deletion. The patient is an 11-year-old female with speech and social interaction difficulties, learning disability, and slight facial dysmorphism, but no other major malformations. An 8 Mb de novo interstitial deletion at 3p14.2-p14.1, from position 60.461.316 to 68.515.453, was revealed by means of array comparative genomic hybridization and confirmed using quantitative reverse-transcription polymerase chain reaction assays. This region includes six genes: FEZF2, CADPS, SYNPR, ATXN7, PRICKLE, and MAGI1, that are known to have a role in neurodevelopment. These genes are located on the proximal side of the deletion. We compare our case with previously well-defined patients reported in the literature and databases.